Necesidad de incorporar en la legislación penal Ecuatoriana la figura jurídica de acumulación de penas, que regule y sancione penalmente a quien cometa delitos atroces de asesinato, secuestro y violación - Ruiz Jaramillo, Pablo Roberto (2012)
The juridical norms that it specifies our current Penal Code, don't offer the necessary guarantees to be able to make valid the rights of the victims of some crime; especially those related with the murder, kidnapping and violation. In a without number of occasions have been able to observe that, when several crimes are made and it is that a single victim exists, the sanctions for the victim are not for each made act, but rather she judges it to him for the most serious and I list; even with the last reformation that the State has implemented, with limiting the accumulation of hardships to a 35 year-old maximum, without caring the made criminal acts and the victims that the same ones leave, giving this way a bankrupt concept of "Accumulation", since it is supposed the hardships they should accumulate without limit, however for our artificial reality, I estimate they should accumulate until a 50 year-old maximum, as they make it penal legislations of neighboring countries and in general from all over the world. With this increment in the accumulation of years in prison, he/she wants to be a balance between the crime and the pain; for example, if we have a criminal that makes two or three crimes that are sanctioned with a pain from 16 to 25 years in prison, an unique pain it is imposed of until maximum 50 years. It is necessary that the State and the entities in charge of offering security, regulate and provide integrity, social, economic, labor, physical and juridical conditions that favor to the development of the society; for it is it that I consider the necessity to carry out the present investigation work, and in passing to outline a new reformation to our Penal Code, in which you/they settle down and offer the necessary guarantees for the victims and the relatives of the same ones, when facing a phenomenon that every time charges more force as it is it the delinquency, we have been able to observe like with the time this type of crimes has evolved and they have become one it seals and social plague, since now is not enough only with getting the material object, but lives in such a natural way they are also snatched that is no longer we very concerned, rather we are finding him something of familiarity. This wrong have been established inside the conceptual, doctrinal and juridical marks; I should point out that it also consists of a significant experimental support, obtained in the application of surveys and interviews, also supplemented with an important study of cases, same that were object of study of the outlined problem. The present investigation has been able to end up establishing the reality in the problem that loosens especially for the lack of guarantees for who we can be victims of some crime, if they are of atrocious character as the murder, kidnapping and/or violation; for I allowed it to offer a reformation proposal to the Penal Code, regarding the increment and accumulation of hardships, at least in these three types of crimes (murder, kidnapping and violation) that are some of the most sinister and that they leave indelible prints in their victims, intending accumulates the hardships in a 50 year-old maximum in prison, when crimes of murder, kidnapping and violation are made.